Advanced mobility flight dynamics restriction to support high availability communication systems - Alhashmi, Fatima; Al-Rubaye, Saba; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Electric Vertical Take-Off and Landing (eVTOL) platforms play a crucial role in Advanced Air Mobility (AAM) initiatives, particularly in urban environments. Ensuring the safety and reliability of communication networks during air traffic operations is paramount, with communication performance heavily reliant on antenna radiation characteristics. Maintaining consistent communication throughout the entire flight is essential for flight success. However, dynamic maneuvers such as banking turns can result in airframe shadowing, where the vehicle's structure obstructs antenna signals, posing a challenge to communication reliability. This paper proposes a model integrated into eVTOL avionics to mitigate airframe shadowing issues and maintain optimal communication availability during normal flight operations. A new algorithm is proposed, and simulation studies analysis are conducted to assess the impact of airframe shadowing on eVTOL communication performance. Additionally, insights are provided to air traffic management (ATM) and pilots regarding optimal look angles to minimize or avoid airframe shadowing effects.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 11 Sustainable Cities and Communities